Assessment of Striga gesnerioides (Willd.) Resistance and Genetic Characterization of Forty-Six Cowpea (Vigna unguiculata (L.) Walp.) Genotypes in Ghana. (23rd June 2020) - Haruna, Peter; Asare, Aaron T.; Kusi, Francis
Abstract : The parasitic weed, Striga gesnerioides, imposes physiological stress on cowpea ( Vigna unguiculata (L.) Walp.) resulting in significant yield loss in the regions of northern Ghana. This warranted identification of resistant cowpeas for sustainable production. The current work aim was to identify Striga -resistant cowpea genotypes and assess their genetic relatedness. Forty-six (46) cowpea genotypes were screened in pots for their reaction to Striga samples obtained from the upper east, upper west, and northern regions of Ghana and validated with C42-2B and 61R-M2 markers involving DNA amplification by PCR assay. Sixteen polymorphic SSR primer pairs were used to assess genetic relatedness among 46 cowpea genotypes. Data were analyzed with PowerMarker V. 3.25 and a dendrogram was generated with MEGA 4. On the whole, 65.2% of the cowpea genotypes had stable resistance to S . gesnerioides from the regions of northern Ghana and 34.8% were susceptible. The C42-2B marker resolved as a single DNA band of 280 bp with segregation efficiency of 80% and 61R-M2 marker as double DNA bands of 320 bp and 380 bp with segregation efficiency of 60% associated with Striga resistance. Sixteen (16) polymorphic SSR primers distinguished all 46 cowpea genotypes into three clusters. Gene diversity ranged from 0.04 to 0.49 with an average of 0.29. The average allele frequency is 0.78, with a mean genetic diversity of 0.29. Polymorphism information content (PIC) varied from 0.08 to 1.00 with an average of 0.55. Therefore, cowpeas with Striga resistance and other desirable traits can be evaluated and released as varieties for farmers to cultivate.